Pervasive Refusal Syndrome: Three Case Reports—Autism as a Predisposing Factor and Gentle Coercion to Shorten Duration of Disorder? - Jarbin, Håkan; Saldeen, Ann-Sofie; Forslund, Carl-Magnus (Case Reports in Psychiatry, 2022)
Background. Pervasive refusal syndrome (PRS) is a severe child psychiatric syndrome not yet included in the international classification and mostly affecting girls aged 7-15 years. Hospital admission and severe loss of function extend for many months and years but most recover. Autism has been suggested as a predisposing factor but largely lacks support for typical cases of PRS. Treatment is not evidence-based and described as requiring a lengthy inpatient stay with a very gradual and sensitive rehabilitation program. Case Presentations. Three cases of pervasive refusal syndrome (PRS) in girls aged 9–16 years are presented to report autism as a predisposing factor and to discuss gentle coercion as part of the management strategy to speed up the lengthy recovery. The cases, which met the proposed criteria and typical background characteristics, were noted with the addition of undiagnosed autism in two cases. The duration of inpatient admission was 8–14 months. Disease duration was 15-36 months. An adequate but negative lorazepam trial to rule out catatonia was carried out. Treatment was in one case successfully expedited with gentle coercion within a transparent management plan. Rehabilitation was slower in PRS with comorbid autism; additionally, accommodations to school and living support needed to be put in place. Conclusions. PRS is a useful clinical entity and best perceived as a primitive reaction to overwhelming stress rather than as catatonia. Autism might be another predisposing factor and needs to be assessed. A psychoeducational approach and a clear management plan support rehabilitation. A gentle coercion might hasten recovery.